2007
DOI: 10.1029/2006gl028896
|View full text |Cite
|
Sign up to set email alerts
|

Is geomagnetic activity driven by solar wind turbulence?

Abstract: The Earth's magnetosphere is a highly dynamical system, which continuously exchanges energy, mass and momentum with the solar wind and the Earth's ionosphere. Existing literature would suggest that particular large amplitude interplanetary Alfvén wave trains might cause intense auroral activities known as High‐Intensity Long‐Duration Continuous Auroral Activity (HILDCAAs), as a result of the magnetic reconnection between the southward magnetic field z component and the magnetopause magnetic fields. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
4
34
0
Order By: Relevance
“…Alfvénic waves in the solar wind, on the other hand, can produce repeated periods of weakly negative IMF, typically between À1 and À10 nT. Several papers suggest that Alfvénic waves within the corotating streams enhance substorm activity (D'Amicis, Bruno, & Bavassano, 2007;McPherron, Weygand, & Hsu, 2008;Tsurutani et al, 1990;Tsurutani et al, 1995), power HILDCAAs (high-intensity long-duration continuous AE activity; Tsurutani & Gonzalez, 1987), and contribute to ring current formation (Søraas et al, 2004). D'Amicis, Bavassaro (2011) andBruno (2015) found out that solar wind fluctuations during the maximum phase of solar cycle 23 (SC23) are highly Alfvénic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alfvénic waves in the solar wind, on the other hand, can produce repeated periods of weakly negative IMF, typically between À1 and À10 nT. Several papers suggest that Alfvénic waves within the corotating streams enhance substorm activity (D'Amicis, Bruno, & Bavassano, 2007;McPherron, Weygand, & Hsu, 2008;Tsurutani et al, 1990;Tsurutani et al, 1995), power HILDCAAs (high-intensity long-duration continuous AE activity; Tsurutani & Gonzalez, 1987), and contribute to ring current formation (Søraas et al, 2004). D'Amicis, Bavassaro (2011) andBruno (2015) found out that solar wind fluctuations during the maximum phase of solar cycle 23 (SC23) are highly Alfvénic.…”
Section: Introductionmentioning
confidence: 99%
“…Roberts and Goldstein (1990) reported that Alfvénic intervals often accompany large and extended auroral activity, although the reverse was not found to be true. They examined intervals around the maximum of solar cycle when the interplanetary Alfvén waves and their effects to geomagnetic activity are more often due to the slow solar wind (Chian et al, 2006;D'Amicis et al, 2007;Gonzalez, Clúa de Gonzalez, & Tsurutani, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…[4] Knowledge about the nature of the deviations from the Parker spiral and the physical mechanisms underlying the deviations is important for a full understanding of the structure of the solar wind plasma and the properties of the heliosphere [Bavassano et al, 1996;Bruno et al, 2007; M. Neugebauer and J. Giacalone, Progress in the study of interplanetary discontinuities, unpublished manuscript, 2009]. The nature of the fluctuations will affect ideas about how energetic particles propagate through the heliosphere [McCracken and Ness, 1966;Sari and Ness, 1969;Qin and Li, 2008] and will affect our understanding of how the solar wind couples to the Earth's magnetosphere through a modification of the Russell-McPherron effect on the Parker spiral magnetic field [Berthelier, 1976;Vassiliadis et al, 2002;Borovsky and Steinberg, 2006a;McPherron and Weygand, 2006] and through the direct effect of solar wind fluctuations on the magnetosphere [Tsurutani and Gonzalez, 1987;Tsurutani et al, 1995;Sibeck et al, 1999;Kataoka et al, 2002;Borovsky and Funsten, 2003;Borovsky and Steinberg, 2006b;D'Amicis et al, 2007]. Finally, a full understanding of the nature and physics of magnetohydrodynamic (MHD) turbulence in the solar wind cannot be obtained until the full physical nature of the fluctuations in the solar wind are understood [Siscoe et al, 1968;Hollweg, 1982;Tu and Marsch, 1995;Bruno et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Bavassano et al, 1998;D'Amicis et al, 2007) characterized the s C -s R distribution at solar minimum and maximum finding a predominance of outward Alfvé nic fluctuations (s C 40), dominated by an excess of magnetic energy (s R o0). At solar minimum, such distribution shows a population for s C ' 1 and s R ' 0, typical of Alfvé nic fluctuations, and a long tail towards s C $0 and s R $ À 1.…”
Section: Discussionmentioning
confidence: 99%